Mosque Islamic Social Enterprises Activities as an Instrument of Inclusion; Evidence from Indonesia - Mohammad H Holle (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2023)
For most countries in the world, including Indonesia, poverty has long been a problem. Poverty alleviation programs are basically focused on alleviating poverty. In order to provide a multiplier impact on society, an Islamic social enterprise financial inclusion approach is needed.The Sabilillah Mosque in Malang City and the Jogokariyan Mosque in Yogyakarta are the areas that are the focus of this research. The experimental information used in the subjective investigation approach is based on field perceptions of events that occurred in the investigation area with a qualitative paradigm.Research findings reveal that two mosques in Indonesia, namely the Jogokariyan and Sabilillah Mosques, in Yogyakarta City and Malang City, East Java, run Islamic social entrepreneurship as an instrument of financial inclusion aimed at alleviating poverty. The method is to maximize the use of zakat, infaq and sadaqah as an impact on changes in people's lives. These two mosques are Islamic social enterprises that help the poor in Indonesia and can become models for other mosques in Indonesia and elsewhere that are adapted to regional conditions and potential.